ENHANCING STUDENTS’ LISTENING SKILL THROUGH VARIOUS LISTENING MATERIALS AND ACTIVITIES OUTSIDE THE CLASSROOM - Aryuliva Adnan (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Listening skill has been a “Cinderella” for years. Many studies show that many teachers pay no attention to listening skills. They tried to skip teaching listening for many reasons such as lack of teaching materials and teaching facilities. Since internet now is the largest sources of teaching materials, there is no reason for an English teacher to skip teaching listening skill.  Listening skill as one of the language skill is needed to be taught, and it needs practice not only in the classroom but also outside the classroom. Differ from the teaching and learning other language skills, the teachers can easily assign students to practice the skills outside the classroom. The teachers do realize that students do not have opportunities to practice their listening skill for the books used are not completed with enough exercises, which the students can practice listening skill at home. Due to the lack of exercises of listening skill found in the listening books, therefore assigning students to practice listening to various listening activities outside the classroom are believed can  enhance  the students listening ability. The activities are watching English movies and videos, listening to English radio/TV news, TV commercial.